Peranan Tiga Pilar dalam Penyelesaian Konflik Tenurial di Taman Wisata Alam Ruteng, Flores, Nusa Tenggara Timur - Kriswoyo, Kriswoyo; Pello, Jimmy; Kaho, Ludji M. Riwu (Bumi Lestari; Vol 19 No 1 (2019)DO - 10.24843/blje.2019.v19.i01.p05, 2019)
Manggarai communities has been in and around the area of Ruteng Recreation Parksince before the establishment. The determination of the area for conservation cause tenure conflictsfor the closure region for access to agricultural and the timber. The conflict resolution involves three elements, namely the government, customs and religion are called the three pillars. This study aims to understand the stages of the conflict tenure in Manggarai, relevant stakeholders and the role of the three pillars in conflict resolution. The study was conducted in four villages with village conflicting criteria and do not conflict in April to May 2016. Acquisition of data using observation, in-depth interviews with a purposive and snowball and secondary data. Analysis of data using analysis of tree conflicts, stakeholders and conflict mapping. The results showed that the cause of the conflict which is the difference value systems which have implications for the disagreement land status and boundaries as well as the uncertainty of access due to rights issues and access. Ruteng Recreation Park area assignment is not determined by the collective perception that lack of support of the parties. Ruteng Recreation Parksetting legislation and its implementation does not guarantee the security of rights and indigenous peoples' access due to constraints of knowledge and understanding of the laws and regulations, resource constraints, regulatory and administrative development issues. The concept of the three pillars was not optimal because it has not reduced the rate of destruction of Ruteng Recreation Park and there were still conflict of encroachment and illegal logging.